Convergence of Inequality Dimensions in China: Income, Consumption, and Wealth from 1988 to 2018 - Haiyuan Wan; Björn Anders Gustafsson; Yingfei Wang (Institute of Labor Economics (IZA), 2024)
Using household data from 1988 to 2018, we confirm that the increase in income inequality in China has come to a halt in recent years but show that inequality in wealth and consumption continues to increase. We report a clear convergence of inequality across the different dimensions of income, consumption, and wealth. Households at the top of one dimension are increasingly located at the top of the other two dimensions. The mechanisms for such convergence across dimensions are analysed, and the savings rate links income and consumption, while capital accumulation is the central mechanism linking income and wealth. In addition, the wealth and income structure contribute to intensifying the convergence trend. We argue that the relatively high level of inequality in China may continue since income, consumption and wealth are increasingly reinforcing each other.
Keywords: D31; I31; P52; 330; return rate of capital; property income; savings rate; economic inequality; convergence mechanism